The Influence of Education Level, Gender, and Age on Workforce Productivity at Pak Matali's Woven Bag SMEs, Junrejo District, Batu City - Kaka, Maria Muda; Nur Ida Iriani; Warter Agustim; Anung Prasetyo Nugroho (International Research & Development for Human Beings (IRDH), 2026)
The purpose of this study is to determine the effect of education level, gender, and age on labor productivity in the Handwoven Bag SME Pak Matali, Junrejo District, Batu City, both partially and simultaneously. This research uses a quantitative method. The sample is determined using total sampling technique, so the entire population is used as the research sample consisting of 32 employees of the Handwoven Bag SME Pak Matali, Junrejo District, Batu City. The data collection technique used by the researcher is a questionnaire. The data analysis method used is multiple linear regression using SPSS 25. The research results prove that the education level has a significant effect on labor productivity in SMEs with a calculated t value of 6.176, gender has a significant effect on labor productivity in SMEs with a calculated t value of 4.562, and age has a significant effect on labor productivity in SMEs with a calculated t value of 4.286. The results simultaneously indicate that education level, gender, and age significantly affect labor productivity in SMEs with an F-count value of 5.052 or 62.9%. This finding proves that improving labor productivity is supported by education level, gender, and age.